ANALISIS PEMBENTUKAN KARAKTER SISWA BERBASIS PENDIDIKAN SENI BUDAYA DI SMAN 1 KERTOSONO NGANJUK - Ratnasari, Kristin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
Schools as formal educational institutions are role models in many ways, including character education. Character education in schools is adjusted to the age level of the mental development of students, formal educational institutions have a responsibility in printing the nation's next generation, competitive with character. Therefore, this study seeks to examine how the strategy of character building students based on arts and culture education is. The results of this study show the first. character education efforts through the development of school culture is to familiarize all students to always apply the school cultures that have been set by the management of SMAN 1 Kertosono, Nganjuk Regency. Students from the beginning of entering school until graduation are instilled with a spiritual moral culture, clean and tidy, love the homeland, loyal friends, always learning and developing school culture as an effort to create a conducive school environment to develop positive characters. Second, the cultural arts learning strategy with character. Strengthening one of the sub-fields of art is intended to optimize the implementation of cultural arts subjects. Taking into account the availability of teaching staff, student interests, facilities and infrastructure. The specification of one of the arts in the educational process will accelerate efforts to build character education.